Hermeneutika Al-Qur’an: Tipologi Tafsir Sebagai Solusi dalam Memecahkan Isu-Isu Budaya Lokal Keindonesiaan - M. Nurdin Zuhdi (UIN Sunan Kalijaga Yogyakarta, 2012)
Religion should be a source of inspiration for the completion of any problems that exist in society. Religion has a very important part in the resolution of current issues that developed in the middle of the race. Here, the Qur'an and the Sunnah as the primary sources of Islam should be a solution to the existing problem. So, how is that al-Qur'an and Sunnah can be a solution for Muslims in facing the current issues? Al-Qur'an and Sunnah should be understood in its context returned in the current era. Interpretation methodology should also experiencing growth. In addition to using the existing methodology konvensional, Indonesia exegetes should be dare to involves contemporary methodologies such as hermeneutics and set humanities others. With the new methodology and adequate regardless of existing methodologies while remaining grounded in the original text, expected actual issues that develop can be resolved.